# Super Subtraction 3: Changing the Minuend & Subtrahend

## Examples:

Case A: 12 - 8 = 4

Case B: 13 - 9 = 4 (1 was added to both the minuend & the subtrahend!)

Case C: 11 - 7 = 4 (1 was subtracted from both the minuend & the subtrahend!)

Notice how the difference remained exactly the same in each case!

### Here's comes the next example with a different difference!

Case A: 14 - 3 = 11

Case B: 15 - 4 = 11 (1 was added to both the minuend & the subtrahend!)

Case C: 16 - 5 = 11 (2 was added to both the minuend & the subtrahend!)

Case D: 13 - 2 = 11 (1 was subtracted from both the minuend & the subtrahend!)

Case E: 12 - 1 = 11 (2 was subtracted from both the minuend & the subtrahend!)

Case F: 14.5 - 3.5 = 11 (0.5 was added to both the minuend & the subtrahend!)

Case G: 13.5 - 2.5 = 11 (0.5 was subtracted from both the minuend & the subtrahend!)

## The change to the minuend & subtrahend can even be a non-integer!

Case A: -7 - (-6) = -1

Case B: -6 - (-5) = -1 (1 was added to both the minuend & the subtrahend!)

Case C: -5 - (-4) = -1 (2 was added to both the minuend & the subtrahend!)

Case D: -8 - (-7) = -1 (1 was subtracted from both the minuend & the subtrahend!)

Case E: -9 - (-8) = -1 (2 was subtracted from both the minuend & the subtrahend!)

Case F: (-7 + i) - (-6 + i) = -1 (i was added to both the minuend & the subtrahend!)

Case G: (-7 - i) - (-6 - i) = -1 (i was subtracted from both the minuend & the subtrahend!)

Case H: (-6 + i) - (-5 + i) = -1 (1 + i was added to both the minuend & the subtrahend!)

Case I: (-8 - i) - (-7 - i) = -1 (1 + i was subtracted from both the minuend & the subtrahend!)